2018
DOI: 10.18203/2394-6040.ijcmph20180776
|View full text |Cite
|
Sign up to set email alerts
|

Burnout among clinicians in tertiary care setting

Abstract: Background: “Burnout” is defined as a state of physical, emotional and mental exhaustion, or a coping mechanism to working conditions that are stressful, demanding and lack of recognition. Effects of burnout are many and can eventually threaten one’s job satisfaction, relationship and also health. High patient load, long working hours, poor logistics and infrastructure support and unreasonable demands from patients make clinicians vulnerable for stress and burnout. Objective was to study the prevalence of burn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“… 9 The present study found that years of work experience were significantly associated with work-related burnout; the studies conducted in Delhi and Andhra Pradesh among nurses and clinicians found that respondents with low years of expertise reported high levels of burnout. 10 , 11 …”
Section: Discussionmentioning
confidence: 99%
“… 9 The present study found that years of work experience were significantly associated with work-related burnout; the studies conducted in Delhi and Andhra Pradesh among nurses and clinicians found that respondents with low years of expertise reported high levels of burnout. 10 , 11 …”
Section: Discussionmentioning
confidence: 99%
“…[8,[11][12][13] Two studies showed a positive association between burnout and female gender, [8,11] while a couple of others did not support this association. [12,13] Positive correlates of burnout include working in clinical departments, especially surgical departments, number of years spent in residency, [8,12] and personality traits such as sociability as well as the self-control and emotionality subconstructs of emotional intelligence (EI), [19] decreased participation in recreational activities, negative encounters with patient or attendants, and lack of perceived support and empathy from senior doctors. [13] Three major changes related to the health-care scenario in India appear to contribute to the increasing trend of physician burnout.…”
Section: Determinants and Mediators Of Physician Burnoutmentioning
confidence: 98%
“…Langade et al, 2016 [11] Medical practitioners 5% [12] Interns and residents [8] All clinicians working in the institute…”
Section: Prevalence Of Burnoutmentioning
confidence: 99%
See 2 more Smart Citations